ANALISIS PENDAPATAN PETANI KAKAO DI KECAMATAN PADANG TIJI KABUPATEN PIDIE - Muhammad Dhiyauddin; Cut Zakia Rizki (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to analyze the income of cocoa farmers in Padang Tiji District, Pidie Regency. Revenue is revenue minus total costs during production. The data used in this study are primary data. The method used is descriptive qualitative, sampling using purposive sampling with a total sample of 93 respondents. The results showed that farmers' income ranged from Rp. 14,085,313 - Rp. 52,715,000 / year. The level of production and price of cocoa sales based on the results of the analysis found that when production increases, the amount of farmers' income is higher and vice versa if production decreases, the number of farmers' income decreases, so when prices rise, the number of farmers' income is higher down, the number of farmers' income also declined. The total production costs incurred on cocoa farming depend on the area of land owned which ranges from Rp. 8,670,313-Rp. 39,660,000. As one of the central areas of cocoa plantations, the government must be able to help farmers in Pidie Subdistrict in terms of business capital, counseling, and marketing of cocoa products to increase farmers' income and be able to increase Pidie District's Original Revenue.Keywords: Income, production costs, land area, price, amount of production